2016
DOI: 10.1111/bcp.13037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of renal impairment on the pharmacokinetics of orally administered deferiprone

Abstract: AimsIn light of the growing recognition of renal disease in thalassemia, it is important to understand the impact of renal impairment on the pharmacokinetics of iron chelators. This study evaluated the pharmacokinetics and safety of the iron chelator deferiprone (DFP) in subjects with renal impairment in comparison with healthy volunteers (HVs).MethodsThirty‐two subjects were categorized into four groups based on degree of renal impairment: none, mild, moderate or severe, as determined by estimated glomerular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…With respect to PK, the results obtained in this trial were similar to those seen in previous studies of deferiprone in healthy subjects, in which deferiprone was shown to be rapidly absorbed from the gastrointestinal tract, appearing in the blood within 5 to 10 minutes and with peak serum concentrations occurring approximately 1 hour after administration in the fasted state (ApoPharma, internal data). They were also comparable to results reported in the literature in both non-ironoverloaded 13 and iron-overloaded subjects. [14][15][16][17] The increase in exposure to deferiprone and deferiprone 3-O-glucuronide was proportional to the increase in dose.…”
Section: Discussionsupporting
confidence: 90%
“…With respect to PK, the results obtained in this trial were similar to those seen in previous studies of deferiprone in healthy subjects, in which deferiprone was shown to be rapidly absorbed from the gastrointestinal tract, appearing in the blood within 5 to 10 minutes and with peak serum concentrations occurring approximately 1 hour after administration in the fasted state (ApoPharma, internal data). They were also comparable to results reported in the literature in both non-ironoverloaded 13 and iron-overloaded subjects. [14][15][16][17] The increase in exposure to deferiprone and deferiprone 3-O-glucuronide was proportional to the increase in dose.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies in subjects with mild to moderate liver dysfunction reported that the disposition of DFP and DFP-G was generally similar among all subjects, regardless of degree of hepatic impairment [14,22]. Similarly, previous studies comparing healthy volunteers with mild to severe renally impaired subjects demonstrated comparable drug exposure and found that no dosage adjustment of DFP is needed in patients with renal impairment [15]. These previous observations are notable because patients with SCD can experience up to a 68% increase in the prevalence of albuminuria with age [23,24].…”
Section: Discussionmentioning
confidence: 80%
“…Deferiprone (Ferriprox®) is an oral iron chelator indicated for treatment of iron overload in transfusion-dependent patients with thalassemia syndromes [ 14 ]. Its use is not associated with renal toxicity and is well tolerated in patients with decreased renal function [ 14 , 15 ]. Furthermore, systemic exposure to deferiprone (DFP) was not altered in subjects with renal impairment, and no dose adjustment was required [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, if a drug has high renal clearance as a percentage of total body clearance in an unchanged form, then mild or moderate renal impairment could alter AUC by twofold or more [5,6]. Conversely, where the percent unchanged drug (or active metabolite) excreted in urine is low, then severe renal impairment may have no effect [7]. In addition, alterations in drug absorption, bioavailability, and plasma protein binding capacity can also occur in a renal impaired population (review in [8]), further affecting drug exposure.…”
Section: Introductionmentioning
confidence: 99%